Karakterisasi Bakteri Potensial Pengurai Plastik di Kawasan Bakau Sine Tulungagung - Salsabila Zahrotul 'Izzah, Annisa; Muhammad Iqbal Filayani (Jurnal Biotek, 2022)
The use of plastic is still favored by most people today, which has increased the amount of plastic waste. One of the bacteria that can carry out plastic bioremediation is found in mangrove ecosystems. The existence of the mangrove ecosystem is found on Sine Tulungagung Beach, but there has never been further exploration regarding the presence of plastic-degrading bacteria. This research was conducted to explore the presence of potential plastic-degrading bacteria in the mangrove area of the Sine Tulungagung coast. This study used a descriptive-qualitative method that began with planting plastic samples in mangrove deposits, followed by taking bacterial samples from the mangrove area of Sine Beach, Tulungagung. 21 bacteria were isolated from the exploration and tested for their ability to reduce the weight of the plastic. Bacteria with the ability to decompose plastic were then identified using morphological (color, shape, edges, elevation, and size) and biochemical (gram staining and catalase enzyme) tests. It was found that the highest plastic weight reduction was 6.97%, with the most characteristics in the form of coccus and gram-negative bacteria.